Teachers’ self-efficacy beliefs, attitudes and concerns about implementing inclusive education in Ghana - Kuyini, Ahmed Bawa (2018)
This study explored teacher self-efficacy, attitudes and concerns about implementing inclusive education in Ghana, using a four part survey questionnaire comprising Teachers’ Background Information, Self-Efficacy About Inclusive Education, Attitudes Toward Inclusive Education and Concerns About Inclusive Education. Data obtained from 134 primary school teachers in two regions were analysed using Descriptive statistics, t-Tests, ANOVA and Correlation procedures. The results indicate that Ghanaian teachers in the study have concerns about inclusive education, less positive attitudes and also have moderate levels of self-efficacy about implementing inclusive education. These findings have implications for sustaining inclusive education and are discussed in relation to contextual variables and student demands.